Economic Arguments and Legal Regulations on Ritual Slaughter in Poland - Dyda, Konrad (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2020)
When regulating ritual slaughter, we need to take into consideration issues related both to the protection of freedom of conscience and religion, the freedom of business activity, and the humane treatment of animals. The economic arguments have an influence on the way ritual slaughter is regulated and generally lead to departing from the original religious purpose of such legal regulations, in favour of protecting economic interests.